The Effect of an E-Learning Design by Ruffini Model in Learning Passing and Lay Up Scoring Skills in Basketball for Female Students - Hayder S. Mohseen (Journal of Global Pharma Technology, 2016)
The present study objectives to develop a pedagogical design in the Ruffini model for the correction of lay-up and the passing of basketball for female students. Learning the impact of the instructional design in the Ruffini model teaches you how to shoot the lay-up and the passing of the basketball for female students. The researcher used the experimental approach of two equal pretest and other measurement sets to fit the nature of the research problem and objectives. Researchers have used the experimental approach of two equal pretest and self-measurement sets to fit the nature of the research problem and objectives. The sample of research (30) was in the experimental group and the same as in the officer, and educational modules were prepared according to the instructional design of the Ruffini model for the skills examined and the main experience was applied to female students for 8 weeks with two educational units per week and with a time of capacity (90) Minutes for one educational unit. The design of the Ruffini model has contributed to the training of the passing and correction of the ladders of the first stage students in the experimental group. One of the most important findings of the researchers is that the design of the Ruffini model has contributed to the learning of the passing and correction of the foot ladders of the first stage students in the experimental group.Keywords: E-learning designs, Ruffini model, Shoot lay-up, the passing and basketball.